Life And Scientific Heritage Of Nuriddin Sobuni Bukhari - Makhsumkhanov Rakhmatkhan Akhmadjanovich, Mamanasirov Fahriddin Nigmatillaevich (International Journal of Advanced Science and Technology, 2020)
The article explores the life, scientific heritage and scientific discussions of Nuriddin SobuniBukhari.